Business perception and knowledge management for using virtual reality in emerging countries - Cosio Borda, Ricardo Fernando (2025)
The objective of this research was to determine the relationship between business perception and knowledge management for the use of virtual reality in companies in emerging countries. An applied methodology with a quantitative approach was used, at a correlational level and as a data collection instrument, a questionnaire was applied for each variable. The result of the study allowed us to identify a positive relationship between both variables. The conclusion of the study indicates that when there is a favorable business perception for the use of virtual reality, knowledge management will be a less complex and more optimal process for companies.